(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The acquisition of vocabulary competency facilitates the development of language skills, particularly in the domain of reading. Currently, the utilisation of visual aids in media-assisted language learning is widely employed on a global scale due to the emergence of technology. Researchers and educators in the area of second language acquisition have achieved notable progress in instructing language learners on the ability to deduce meaning from contextual cues during the process of reading. This research employed a mixed-methods approach, combining online questionnaire and focus groups to examine intentional content learning using multimodal vocabulary instruction of students. The findings of the research demonstrated a significant enhancement in participants’ knowledge and additional vocabulary acquisition in the focus group. The focus group demonstrated an improvement in vocabulary and content knowledge, which can be attributed to the students’ positive reactions in the classroom and the presence of multimodal contextual instruction in the classroom, and repeated exposure to target words in the learning instructions. The utilisation of intense learning as a means to incorporate subject matter and language instruction for specific objectives. In this research, we propose a method that may enhance learners’ motivation to develop vocabulary in a second language, as well as their proficiency and fluency in the language. The implementing multimodal vocabulary is practical option for educators and an effective tool for enhancing students’ learning and involvement.